Association of Daily Activities With Maternal–Child Bonding, Parenting Self-Efficacy, Social Support, and Parenting Behaviors Among Survivors Living in an Intimate Partner Violence Shelter: A Daily Diary Study - Ravi, Kristen E. (Journal of interpersonal violence, 2024)
Following a traumatic event such as intimate partner violence (IPV), survivors often experience stress related to the violence. These high levels of stress related to IPV can be associated with the daily activities of survivors and their relationships with their children, such as maternal–child bonding. The purpose of the current study is to explore the relationship between daily activities, daily stress levels, parenting self-efficacy and behaviors, and maternal–child bonding among survivors living in an IPV shelter using an ecological momentary assessment (EMA) methodology. Twenty-five mothers living in an IPV shelter in two states in the Southern United States completed a baseline survey and completed electronic daily diaries for 14 days. Higher daily stress was associated with the number of times the mothers met with the case manager. Higher daily stress was also related to lower parenting self-efficacy. The number of case management appointments and legal appointments were positively correlated with a higher bonding score. More social support was associated with more positive parenting. IPV and post-traumatic stress disorder symptoms were not significantly associated with maternal–child bonding, parenting behaviors, or parenting self-efficacy. Findings suggest that screening for maternal support may be particularly important for positive bonding and positive parenting. Findings also lend preliminary insight into practical places where service providers could act to protect the bonding process or mitigate risks to impede it. Future research should include objective data about the mother’s emotions and her interactive behavior with her child. There is also a need to consider how federal programs fund and incentivize service providers to focus on mother–child dyads and how they can tailor services that promote bonding.